THE IMPACT OF EDUCATION AND INVESTMENT ON POVERTY IN INDONESIA - Aulia, Rizky Muhammad; Herlitah; Nurjanah, Siti (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
Poverty is a problem wich faced by various country in the world, one of them is Indonesia. Several provincein Indonesia still have a large number of poor people, Papua and West Papua Province have percentage ofpoor people of 27.43% and 22.66% in 2018. In addition, the length of schooling in these province isconsecuentively amounted to 6.52 and 7.27 year. This study aims to determine the effect of the level ofeducation and investment on poverty in Indonesia. This study used a panel data of 12 provinces inIndonesia, namely, Papua, West Papua, Maluku, North Maluku, West Sulawesi, Gorontalo, SoutheastSulawesi, Central Sulawesi, South Sulawesi, North Sulawesi, West Nusa Tenggara, and East NusaTenggara Province in time 2016-2018. The theory used in this research is Keynesian Theory, this theorystate that by increasing education and investment, it can be a solution to reduce poverty. The dataprocessed using Eviews 11. Result shows that the level of education has a negative significant effect onpoverty and investment has negative insignificant on poverty.